In memoriam: Jefferson Foote. Issue 1 (1st January 2021) - Ward, E. Sally; Jones, Peter; Buss, Tim; Rada, Cristina; Winter, Gregory; Willson, Richard
ABSTRACT: In a scientific career that spanned over three decades, Dr. Jeff Foote made seminal contributions to antibody humanization and the biophysical aspects of antibody recognition. In this Perspective, we discuss his life and work.